Exploring shared control in upper primary school learners working with an adaptive learning technology - Kooi, Rianne; Knoop-van Campen, Carolien; Segers, Eliane; Molenaar, Inge (Frontline Learning Research, 2026)
This study explored how learners engage in shared control in math in Adaptive Learning Technologies (ALT). In shared control, learners adjust task difficulty (easy, medium, or hard), while the ALT selects tasks based on performance. These adjustments to task difficulty influence the probability of solving the next task correctly. This study aimed to understand (1) differences in how learners use shared control and (2) how this relates to general math ability, regulation of practice behaviour (number of finished problems and accuracy), and learning outcomes. In this exploratory study, 98 grade 5 learners practiced three math topics using an ALT combined with an app, including personalised visualisations of learners’ real-time progress on the math topics and shared control selection options. Results showed four clusters reflecting differences in learners’ use of shared control in quantity and direction of task difficulty changes: learners making no changes (cluster 1), learners making some changes preferring hard difficulty (cluster 2) or easy difficulty (cluster 3), and learners who frequently changed across all task difficulties (cluster 4). Shared control was related to general math ability and influenced learners’ regulation of practice behaviour. Although a comparison with the ALT control was absent, learners seem to choose task difficulties in line with their needs and benefit from these choices, resulting in learning gain. From a self-regulated learning perspective, this indicated how learners engaged in regulation and were aware of their needs.